Therapeutic efficacy of lenvatinib in nonviral unresectable hepatocellular carcinoma. Issue 11 (22nd October 2021) - Tomonari, Tetsu; Sato, Yasushi; Tanaka, Hironori; Mitsuhashi, Takeshi; Hirao, Akihiro; Tanaka, Takahiro; Taniguchi, Tatsuya; Okamoto, Koichi; Sogabe, Masahiro; Miyamoto, Hiroshi; Muguruma, Naoki; Takayama, Tetsuji
Abstract: Aim: To investigate the therapeutic effect of lenvatinib (LEN) in liver disease etiology, especially nonviral hepatocellular carcinoma (HCC). Methods and Results: Sixty‐seven patients with unresectable advanced HCC (u‐HCC) treated with LEN and consisting of 26 hepatitis C virus (HCV), 19 hepatitis B virus (HBV), 11 alcohol, and 11 nonalcoholic steatohepatitis (NASH) cases were retrospectively recruited. Univariate and multivariate Cox proportional hazard models were used to determine predictive factors for survival. The objective response rate in the nonviral (alcohol and NASH) group was higher than that in the viral group (59.1% [13/22] vs. 46.7% [21/45]). Progression‐free survival was significantly longer in the nonviral group than in the viral group (13.7 vs. 6.6 months; hazard ratio [HR] 0.324; 95% confidence interval [CI] 0.174–0.602; P  < 0.01). Similarly, median overall survival (OS) was significantly longer in the nonviral group than in the viral group (not evaluable vs. 15.9 months; HR = 0.277; 95% CI = 0.116–0.662; P  < 0.01). Multivariate analysis revealed that portal vein invasion (HR = 5.327, P  = 0.0025), treatment line (HR = 0.455, P  = 0.023), and etiology (HR = 0.180, P  = 0.00055) were significant independent factors associated with OS in u‐HCC patients treated with LEN. Conclusion: Our results suggest that LEN is more effective against nonviral u‐HCC than against viral u‐HCC. Abstract : Kaplan–Meier analysis of progression‐free survival among patients with unresectable advanced hepatocellular carcinoma treated with lenvatinib according to etiology. The PFS in the non‐viral group was significantly longer than that in the viral group. Our results suggest that LEN is more effective against non‐viral u‐HCC than against viral u‐HCC.